(untitled) (Swiss Medical Weekly, 2024)
The choice of modality of treatment for unruptured intracranial aneurysms is based on various clinical aspects and the patient’s preference. Financial considerations should not be among these. To evaluate any financial variations between endovascular and microsurgical treatment of unruptured intracranial aneurysms in the Swiss healthcare system, we retrospectively reviewed 100 consecutive aneurysm cases treated as inpatients in our institution. Case-based financial data were collected (revenues, costs, net earnings) and compared between the treatments. Among 100 consecutive aneurysm cases treated at our institution (2021–2023), 58 were unruptured intracranial aneurysm. Treatment was endovascular in 33, microsurgery in 23 and conservative/antibiotic in 2 cases. Length of stay (but not duration in the intensive care unit) was longer after microsurgical treatment. Total median revenues (public insurance, private insurance, material reimbursement) were Swiss Francs (CHF) 30,012.25 with a maximum of CHF 125,337.20 and a minimum of CHF 9543.25. No marked difference was found between the treatment groups (endovascular and microsurgery). Despite the fact that median net earnings per patient were positive (CHF 3655.03), more than one third of all cases led to a net loss for the hospital with a tendency for more stable net earnings in microsurgery cases. The only factor associated with a higher risk of net loss per case was higher implant costs in endovascular cases. Reimbursement within the Swiss healthcare system does not promote financial bias for decision-making in treatment modality for unruptured intracranial aneurysm. The fact that one third of all cases does not result in positive net earnings (even in the highly paid unruptured intracranial aneurysm sector), although overall net earnings were positive, should be monitored – especially in times of rising costs.